Measure To Improve Detection of Smear Positive Cases Under RNTCP: Comparison Of 2 Sputum Examinations Versus 3 Sputum Examinations - Rahul Parmar; Rajendra K Baxi (Medsci Publications, 2012)
Background: RNTCP recommends examination of three sputum smears for diagnosis of TB. This may not be practicable under all conditions, especially in difficult areas. It further adds to the laboratory workload, cost of diagnosis and causes inconvenience to patients as well as for the health system. Objectives: The present study was undertaken to compare the efficiency of sputum examination in detecting the smear positive TB cases among the chest symptomatics with 2 sputum examinations Vs 3 sputum examinations. Methods: A cross sectional study including sputum positive pulmonary tuberculosis patients from 2 Tuberculosis Unit (5 Designated Microscopic Centre) of Municipal corporation of Vadodara. Results: The study conducted in the fourth quarter included 143 (23.1 percent) smear positive cases of TB. Dependence on the first specimen (spot) and third specimen (spot) could detect 88.1 percent and 89.5 percent of the sputum positive patients' respectively, while morning specimen could detect 97.3 percent of the sputum positive patients. Comparison of 1st Vs 2nd and 2nd Vs 3rd showed a significant difference at P < 0.01. Repeat sputum Examination in only 11 patients out of 475 TB suspects identified 9% (1/11) smear positive cases. Conclusion: Two sputum smear examinations (one spot & one early morning specimen) are sufficient for diagnosis of tuberculosis Patients.